The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1158/1078-0432.ccr-06-0263
|View full text |Cite
|
Sign up to set email alerts
|

Dominant-Negative Fibroblast Growth Factor Receptor Expression Enhances Antitumoral Potency of Oncolytic Herpes Simplex Virus in Neural Tumors

Abstract: Purpose: Oncolytic herpes simplex viruses (HSV) appear to be a promising platform for cancer therapy. However, efficacy as single agents has thus far been unsatisfactory. Fibroblast growth factor (FGF) signaling is important for the growth and migration of endothelial and tumor cells. Here, we examine the strategy of arming oncolytic HSV with a dominant-negative FGF receptor (dnFGFR) that targets the FGF signaling pathway. Experimental Design: A mouse Nf1:p53 malignant peripheral nerve sheath tumor (MPNST) cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 41 publications
0
57
0
Order By: Relevance
“…7,8 We found that TSA had a suppressive effect on the growth of oral SCC cells at 0.3 mM, but its effect was insufficient at 0.1 mM. When TSA was combined with R849, cell viability was decreased more strongly than with R849 only, indicating that TSA promoted the antitumor activity of the g 1 34.5 genedeficient HSV-1 mutant.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…7,8 We found that TSA had a suppressive effect on the growth of oral SCC cells at 0.3 mM, but its effect was insufficient at 0.1 mM. When TSA was combined with R849, cell viability was decreased more strongly than with R849 only, indicating that TSA promoted the antitumor activity of the g 1 34.5 genedeficient HSV-1 mutant.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, recent studies have focused on the effect of combining oncolytic virotherapy with chemotherapy or construction of viruses encoding therapeutic transgenes. [4][5][6][7][8][9] The ubiquitous nuclear factor NF-kB is a critical regulator of the expression of numerous genes implicated in immune and inflammatory responses, cellular proliferation and differentiation and cell survival. 10,11 It is activated by a broad variety of stimuli, such as growth factors, cytokines, ionizing radiation, ultraviolet light, chemotherapeutic drugs and bacterial and viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…19 Oncolytic HSV encoding dominant-negative fibroblast growth factor receptor or antiangiogenic protein platelet factor-4 led to significant reduction in tumor vasculature and as a result, significantly enhanced therapeutic efficacy. 20,21 Others have engineered oncolytic virus replication to be activated by tumor matrix metalloproteinases (MMP), 22 and shown that MMP-8 gene delivery enhanced the efficacy of oncolytic adenovirus. 23 An alternative approach is to coadminister therapeutic agents with the virus.…”
Section: Targeting the Tumor Microenvironment Enhances Viral Spread Amentioning
confidence: 99%
“…31 It has also been shown that adenovirusinduced ERK activation is critical to viral replication. 43 Oncolytic viruses can also be 'programmed' to replicate in cells through certain cellular signaling activities, such as b-catenin, 44 to carry therapeutic transgene that targets tumorigenic pathways, 20 or retargeted to cellular receptors that are essential for signaling (for example, epidermal growth factor receptor (EGFR)). 45 Novel oncolytic virus species are being explored As most oncolytic viruses have produced less than optimal efficacy in clinical trials as single agents, there is great interest in exploring novel viral species.…”
Section: Genetic Engineering Of Oncolytic Viruses Targets Cancer Signmentioning
confidence: 99%
“…Subsequent studies have examined incorporation of specific transgenes designed to augment the oncolytic HSV-mediated tumor cell killing capacity. Liu et al 87 have demonstrated that incorporation of the dominant-negative FGF receptor into an oncolytic HSV resulted in improved killing of both MPNST cells and endothelial cells as compared with the effect of oncolytic HSV alone or transfection with dominant-negative FGF receptor alone, when studied in vitro. The oncolytic HSV with dominant-negative FGF receptor demonstrated greater in vivo inhibition of angiogenesis and tumor growth than did an oncolytic HSV vector without the dominant-negative FGF receptor.…”
Section: Schwann Cell-specific Approachesmentioning
confidence: 99%